Functional Connectivity Within the Executive Control Network Mediates the Effects of Long-Term Tai Chi Exercise on Elders’ Emotion Regulation - Liu, Zhiyuan; Wu, Yuyan; Li, Lin; Guo, Xiuyan (Frontiers in Aging Neuroscience, 2018)
Previous research identified the effects of tai chi exercise on elders’ executive control or its effect on emotion regulation, respectively. However, few works have attempted to reveal the relationships between tai chi, executive control, and emotion regulation in one study. The current resting-state study investigated whether the impact of tai chi on elders’ emotion regulation was mediated by resting-state functional connectivity within the executive control network. A total of 26 elders with long-term tai chi experience and 26 demographically matched healthy elders were recruited. After the resting-sate scan, both groups were required to complete a series of questionnaires, including the Five Facets Mindfulness Questionnaire (FFMQ), and a sequential decision task, which offered an index of the subjects’ emotion regulation ability by calculating how their emotion response could be affected by the objective outcomes of their decisions. Compared to the control group, the tai chi group showed higher levels of non-judgement of inner experience (a component of the FFMQ), stronger emotion regulation ability, and weaker resting-state functional connectivity between the DLPFC and the MFG. Moreover, the functional connectivity between the DLPFC and the MFG in the tai chi group fully mediated the impact of non-judgement of inner experience on their emotion regulation ability. These findings highlighted that the modulation of non-judgement of inner experience on long-term tai chi practitioners’ emotion regulation was achieved through decreased functional connectivity within the executive control network.